Public–Private Partnerships as Drivers of Sustainable Business Innovation in India’s Infrastructure Sector - Nisha Jain; Jyoti Prakash Rath (The Indonesian Institute of Science and Technology Research, 2026)
Public–Private Partnerships (PPPs) are increasingly recognized as key enablers of sustainable innovation in India’s infrastructure sector. This paper examines how PPPs foster innovation in environmental sustainability, technological adoption, and stakeholder engagement across critical domains, including transport, energy, urban development, and smart cities. Through a review of literature and multiple case studies, we find that PPPs leverage private-sector expertise to introduce green technologies (such as renewable energy integration and advanced construction materials), improve service efficiency, and engage diverse stakeholders in infrastructure delivery. Case studies from India’s highway networks, renewable energy parks, municipal services, and smart city initiatives illustrate that well-structured PPPs can accelerate environmentally sustainable solutions while sharing risks and rewards between public and private partners. The findings are discussed in the context of sustainable development goals, and policy implications are outlined to enhance the role of PPPs as catalysts for innovation and long-term sustainability in infrastructure.